Implementation of hospital governing boards: views from the field - McNatt, Zahirah; Thompson, Jennifer W; Mengistu, Abraham; Tatek, Dawit; Linnander, Erika; Ageze, Leulseged; Lawson, Ruth; Berhanu, Negalign; Bradley, Elizabeth H (BMC health services research, 2014)
Background Decentralization through the establishment of hospital governing boards has been touted as an effective way to improve the quality and efficiency of hospitals in low-income countries. Although several studies have examined the process of decentralization, few have quantitatively assessed the implementation of hospital governing boards and their impact on hospital performance. Therefore, we sought to describe the functioning of governing boards and to determine the association between governing board functioning and hospital performance. Methods We conducted a cross-sectional study with governing board chairpersons to assess board (1) structure, (2) roles and responsibilities and (3) training and orientation practices. Using bivariate analysis and multivariable regression, we examined the association between governing board functioning and hospital performance. Hospital performance indicators: 1) percent of hospital management standards met, measured with the Ethiopian Hospital Reform Implementation Guidelines and 2) patient experience, measured with the Inpatient and Outpatient Assessment of Healthcare surveys. Results A total of 92 boards responded to the survey (96% response rate). The average percentage of EHRIG standards met was 58.1% (standard deviation (SD) 21.7 percentage points), and the mean overall patient experience score was 7.2 (SD 2.2). Hospitals with greater hospital management standards met had governing boards that paid members, reviewed performance in several domains quarterly or more frequently, developed new revenue sources, determined services to be outsourced, reviewed patient complaints, and had members with knowledge in business and financial management (all P-values < 0.05). Hospitals with more positive patient experience had governing boards that developed new revenue sources, determined services to be outsourced, and reviewed patient complaints (all P-values < 0.05). Conclusions These cross-sectional data suggest that strengthening governing boards to perform essential responsibilities may result in improved hospital performance.